2020
DOI: 10.1002/aoc.6122
|View full text |Cite
|
Sign up to set email alerts
|

Arene diruthenium(II)‐mediated synthesis of imines from alcohols and amines under aerobic condition

Abstract: The utility and selectivity of the newly synthesized dinuclear arene Ru(II) complex were demonstrated towards the synthesis of imines from coupling of alcohols and amines in the aerobic condition. Analytical and various spectral methods have been used to establish the unprecedented formation of the new thiolato‐bridged dinuclear ruthenium complex. The molecular structure of the titled complex was evidenced with aid of X‐ray crystallographic technique. A wide range of imines were obtained in good‐to‐excellent y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
(15 reference statements)
0
3
0
2
Order By: Relevance
“…It has been reported that pincer transition metal complexes such as pincer Ru, Ni, and Mn complexes can catalyze acceptorless dehydrogenative coupling of alcohols with appropriate nucleophilic species [5d–g,6a,b,7,8,9a,b,g,h,10] . In our previous studies we synthesized N,N,P‐pincer nickel complex [Ni1] (Figure 1) and studied its catalysis in activating C−X (X=F, N, O) bonds [14] .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that pincer transition metal complexes such as pincer Ru, Ni, and Mn complexes can catalyze acceptorless dehydrogenative coupling of alcohols with appropriate nucleophilic species [5d–g,6a,b,7,8,9a,b,g,h,10] . In our previous studies we synthesized N,N,P‐pincer nickel complex [Ni1] (Figure 1) and studied its catalysis in activating C−X (X=F, N, O) bonds [14] .…”
Section: Resultsmentioning
confidence: 99%
“…Ao longo dos anos, várias adaptações foram sendo realizadas, introduzindo-se ácidos de Lewis para facilitar a reação ou trocando as montagens complexas de destilação por procedimentos mais simples, nomeadamente de adsorção, envolvendo agentes exsicantes, como peneiros moleculares [17][18][19]. Mesmo assim, a maioria destas metodologias continuava a apresentar limitações, sendo razoavelmente eficientes apenas para substratos específicos, apresentando tempos de reação longos e/ou requerendo condições vigorosas [20][21][22].…”
Section: Iminas Intermediários-chave Em Química Orgânicaunclassified
“…Neste contexto, metodologias sintéticas alternativas foram sendo desenvolvidas, envolvendo a reação aza-Wittig [23] ou métodos oxidativos, como a oxidação de aminas secundárias [24], a condensação oxidativa de aminas primárias [25] ou o acoplamento de álcoois e aminas na presença de um oxidante [26] (Esquema 3). No entanto, o uso de reagentes tóxicos e a obtenção de uma baixa economia atómica, bem como uma baixa seletividade são frequentemente observados nestes protocolos [19,21,27].…”
Section: Iminas Intermediários-chave Em Química Orgânicaunclassified
“…In recent years, various homogeneous and heterogeneous noble and non-noble metal catalysts have been explored for the direct coupling of alcohols and amines to imine. Ruthenium-based catalysts are among the most active and effective metal-based catalysts in this field, catalyzing this dehydrogenative condensation reaction either with an oxidant (typically, O 2 or air) or even in the absence of any oxidants under an inert atmosphere. While the latter could largely avoid overoxidation of alcohols to carboxylic acids, it might also be faced with a significant decrease in reaction selectivity caused by the formation of amine byproducts as a result of the reaction of imine products with the hydride species generated during the dehydrogenation process. , Moreover, some of the catalytic systems presented for the coupling of alcohols with amines under inert conditions have drawbacks such as using large amounts of poorly accessible, expensive, complex, and yet nonrecyclable homogeneous catalysts, using additives, requiring high reaction temperatures, and needing to conduct the reactions under an Ar/N 2 atmosphere. Therefore, it seems that the aerobic oxidative coupling of alcohols and amines, especially by employing heterogeneous and recoverable catalytic systems, is still an active and preferable approach to the synthesis of imines. However, while the utilization of various Ru catalysts, either in the form of homogeneous or heterogeneous catalytic systems, has been extensively established in the aerobic oxidation of alcohols and/or amines, the use of Ru-based catalytic systems in the one-pot tandem synthesis of imines through the selective oxidative coupling of alcohols and amines is a multifaceted and relatively less explored process.…”
Section: Introductionmentioning
confidence: 99%